ANALISIS DAYA SAING EKSPOR KOPI PROVINSI SUMATERA UTARA DI INDONESIA - Gesy Indasari; Endang Sari Simanullang; Faoeza Hafiz Saragih (Fakultas Pertanian, Universitas Riau, 2016)
North Sumatra Province is one of the largest coffee production Province in Indonesia. The type coffee produced in North Sumatra province are coffee arabica and robusta. North Sumatera Province had no doubt in exporting palm oil commodity, and rubber to many countries. North Sumatra Province can not just rely on both of that commodities and therefore it is necessary to other alternatives such as coffee. Volume and value of coffee exports fluctuated reflecting the competitiveness of North Sumatra Province coffee needs to be improved. The aim of this research to analyze the comparative advantage, a tendency to be exporter or importer of coffee and coffee export projection of North Sumatra Province. The method used is the Revealed Comparative Advantage (RCA), Trade Specialization Index (TSI) and Trend. The result showed that North Sumatera Province coffee has a competitiveness and as coffee exporter and the projection of coffee export was positive for the next 5 years.